BODY IMAGE AND SELF-ESTEEM: META-ANALYSIS STUDY - Della Widasuari; Ananta Yudiarso (Universitas Bunda Mulia, 2021)
Self-esteem the ways when individuals view their lives. Body image wilf form self-esteem that affect the ability to explore themselves. This article was created to statistically strengthen the relationship between body image and self-esteem. This study aims to determine the relationship between self-esteem and body image using a meta-analysis research method. This study involved 16 journals with 16 correlatoin coefficients. The statistical test shows that body image and self-esteem have a small effect size correlation (r=0,187) with 95,6% CI, and P value 0,32 (α=0,05), and the results of egger bias indicator showed there was no publication bias. The research results indicate that body image and self-esteem that there is in-direct effect relationship.